ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPAS PADA MATERI SUMBER DAYA ALAM KELAS IV SDN 1 UJUNG TANJUNG - Ali Jenar; Sukardi; Mega Kusuma Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking is the ability to analyze information logically and objectively in order to make decisions or solve problems. Based on the results of observations at SDN 1 Ujung Tanjung, it is known that the learning outcomes of fourth grade students in IPAS subjects have not yet reached the Criteria for Achieving Learning Objectives (KKTP). In addition, student activeness and their critical thinking skills are also still low. This study aims to analyze the critical thinking skills of fourth grade students in IPAS learning, especially on natural resources material. The object of this research was selected based on purposive sampling technique because to determine the research sample in accordance with certain criteria so that the sample taken is in accordance with the research objectives, the informants of this study were grade IV students of SDN 1 Ujung Tanjung to conduct a critical thinking ability test totaling 30 students and grade IV teachers of SDN 1 Ujung Tanjung who provided information about the situation and conditions of the educational setting. The method used is qualitative with a descriptive approach through field research, to get an in-depth picture of students' critical thinking skills. In this study, qualitative data were obtained using test techniques, interviews, and documentation. While primary sources, from the results of critical thinking ability tests, interview results, and documentation. The results showed that students' critical thinking skills were still at a low level. Of the 30 students sampled, 8 students (26.67%) were in the high category, 9 students (30%) in the medium category, and 13 students (43.33%) in the low category. This finding indicates the need to apply more effective learning strategies to improve students' critical thinking skills in IPAS learning